A Comparative Study on the Performance of Fiber-Based Biosorbents in the Purification of Biodiesel Derived from Camelina sativa - Yang, Jie; He, Quan Sophia; Niu, Haibo; Corscadden, Kenneth; Caldwell, Claude (Journal of Technology Innovations in Renewable Energy, 2017)
Biodiesel has received great interest as a promising substitute for petrodiesel. Biodiesel purification which follows the transesterification process is typically carried out using a wet washing process that generates large amounts of wastewater. Consequently, alternative methods are emerging as sustainable options for biodiesel purification. One of such methods is a dry washing process. In this paper, the performance of three dry washing media (commercially available BD-Zorb, sawdust and wood shavings) were evaluated as potentially suitable options for the purification of biodiesel derived from Camelina sativa. The results indicate that for the crude camelina biodiesel with an initial soap content of 9007 ppm, BD-Zorb exhibited the best purification performance. The soap removal capacity of BD-Zorb, sawdust, and wood shavings was 51.1 mL/g, 24.4 mL/g, and 9.4 mL/g respectively. The primary mechanism of soap removal using sawdust and wood shavings media was physical filtration and adsorption. While for adsorbent BD-Zorb, soap removal mechanism included adsorption and ion exchange due to the existence of a small amount of resins. The ion exchange led to a high acid number (1 mg KOH/g) of the purified biodiesel, and failed to meet the ASTM D6751 specifications (<0.5 mg KOH/g).